Fabrication of an N-doped mesoporous bio-carbon electrocatalyst efficient in Zn–air batteries by an in situ gas-foaming strategy. Issue 100 (29th November 2019) - Wang, Hong; Li, Wei; Zhu, Zhiwei; Wang, Yijuan; Li, Pan; Luo, Hao; Xiao, Zhuangwei; Wang, Jianzhi; Tian, Qifeng; Xue, Yanan; Yu, Faquan
Abstract : An N-doped bio-carbon catalyst with a hierarchical interconnected macro/meso-porous structure and high specific surface area exhibited significantly enhanced electrocatalytic activity. Abstract : A nitrogen doped bio-carbon catalyst with high specific surface area and a hierarchical interconnected porous structure was fabricated by an in situ gas-foaming strategy from sodium alginate and ammonium chloride. The optimized catalyst displays a fabulous ORR activity, providing a facile approach for the mass production of metal-free bio-carbon catalysts in fuel cells and metal–air batteries.